Effect of Mannanase on Broiler Performance, Ileal and In-vitro Protein Digestibility, Uric Acid and Litter Moisture in Broiler Feeding - Saki, A.A.; Mazugi, M.T.; Kamyab, A. (International Journal of Poultry Science, 2004)
Protein digestibility and uric acid excretion may play the vital role in feed efficiency and consequently effect on broiler performance. Five hundred unsexed Arian day old chickens were placed after pre-starter feeding (10 days) in 22 pens with 23 chickens in each. This study was modulated in two levels of Mannanase (Tread mark of Hemicell enzyme) enzyme (0 and 5 kg/ton) and three levels of metabolizable energy (3000, 2900 and 2850 kcal/kg). Six treatments were arranged and statistical status was in complete random design (CRD) by management in factorial (2 x 3) in this experiment. There is no any significant effect on IIeal protein digestibility by different levels of enzyme. Where this digestibility was significantly higher (P<0.05) by 2900 kcal/kg metabolizable energy (ME) compared to other level of energy (Table 5). Ileal protein digestibility was significantly higher (P<0.05) by interaction between 2900 Kcal/kg ME and different levels of enzyme in comparison to 2850 kcal/kg ME with zero level of enzyme. Dry matter in-vitro digestibility (DMID) was greater significant (P<0.05) by using enzyme compared with no enzyme treatment Increased significantly in-vitro dry matter digestibility (P<0.05) was observed by 2850 kcal/kg ME compared to other level of energy. Otherwise increasing significant (P<0.05) dry matter digestibility was found by 2850 kcal/kg ME energy and high level of enzyme compared to other treatment with exception of 2850 kcal/kg ME and zero level of enzyme. The similar trend was indicted on in-vitro protein digestibility (CPID) regarding enzyme reaction. In addition this item was significantly decreased (P<0.05) by 3000 kcal/kg ME in comparison to other levels of energy. The highest significant rate (P<0.05) was appeared on in-vitro protein digestibility by interaction between of 2850kcal/kg ME and high level of enzyme with exception of 2900 kcal/kg ME and high amount of enzyme. Although no significant reaction was observed in uric acid excretion by energy but this parameter significantly decreased (P<0.05) by high level of enzyme. In their interaction huge declining was shown by 3000 kcal/kg ME and high level of enzyme in comparison to 2900 kcal/kg ME and low level of enzyme. No significantly response was shown regarding litter moisture by all treatments. No response has been appeared in feed intake (FI) regarding enzyme level but higher significant (P<0.05) body weight (BW) was indicated by high level of enzyme in the end of experiment (42 days of age). Growth rate (GR) was greater significant (P<0.05) by using high level of enzyme but no differences was obtained in feed conversion ratio (FCR) in concern to different levels of enzyme in the end of this study. The results of this study have shown that hemicell enzyme could improve performance and increased IIeal protein digestibility, in-vitro DM, CP digestibility and reduction in uric acid excretion which may lead to reduce protein utilization in broiler feeding